Prevalence, transmission dynamics of hydatidosis in slaughtered animals in Dodoma municipality, Tanzania - Mosha, Idda H.; J. Ezekiel, Mangi; Mawaka, Miraji A.; S. Tarimo, Donath (International Journal of Scientific Research and Management (IJSRM), 2022)
BackgroundCystic Echinococcosis (CE) has been reported to exist both in humans and animals affecting people with their livestock. The study aimed to examine the prevalence of CE in slaughtered animals; practices facilitating transmission and perceived risk of human infection in Dodoma municipality, Tanzania.MethodsA quantitative cross-sectional study was conducted. Prevalence of CE was determined by physical examination of organs from slaughtered animals. Collected cysts were preserved in formalin, and then transported to Parasitology laboratory for establishment of fertility. A questionnaire was used to collect data. Data analysis was done by Statistical Package of Social Sciences software. Frequency tables on the prevalence of hydatidosis fertility rate of hydatid cysts, demographic characteristics, awareness, knowledge, risk perception and practices were tabulated. Chi square test was used to test relationship between variables related to awareness and knowledge on hydatidosis. Results Inspected animals for CE in different organs were 1,485, among them700 were cattle, 430 goats and 355 sheep. Overall prevalence of CE in all animals was 4.7%; and 7.6%, 2.1% and 2.3% for cattle, goats and sheep, respectively. Fertility rate was; 50.9% in cattle, 33.3% in goats, and 50% in sheep. The questionnaire involved 361 respondents. Majority 91.7% had low knowledge, 8.3% moderate on CE. Backyard-slaughtering, free-range dogs and livestock keeping, feeding offal to dogs and close relationship between dogs, humans and livestock kept the community at risk of acquiring CE. Conclusion CE was high among ruminant animals in Dodoma. Majority of participants had limited awareness on modes of transmission and practices that put them at risk. Close proximity to dogs indicates the potential risk for human infection. Collaboration between medical and veterinary sectors is recommended to raise community awareness and address the problem.